Yu.N. Verkhovsky. Letters to G.I. Chulkov and N.G. Chulkov - Alexander L. Sobolev (Литературный факт, 2023)
It is the first time that the letters of Yury Nikandrovich Verkhovsky to Georgy Ivanovich and Nadezhda Grigorievna Chulkov are published in their entirety. This correspondence, which lasted almost 30 years, represents a significant source of knowledge about the history of Russian modernism: among those mentioned are A.A. Blok, V.I. Ivanov, A.M. Remizov, M.A. Tsiavlovsky, M.A. Zenkevich, A.S. Dolinin, Yu.N. Tynyanov, A.A. Akhmatova, A.N. Tolstoy, and many others. Particular letters are related to particular events of the cultural life: the poetry book series of the “Academia” publishing house; the famous “case of a monkey tail,” which has induced the rift in the literary world; Verkhovsky’s work on the commentary to the collected works of Y.A. Baratynsky; the attempts to publish the prose experiments of the prominent archaeologist B.L. Bogayevsky; the receptions of the lost novels of A.D. Skaldin. Especially noteworthy are materials to the letters author’s own life history: the article reveals the circumstances of the publication, existence, and reception of the collection of his poems “Sun in captivity,” the longstanding publication attempts of his D. Bocaccio’s “Ninfale fiesolano” translation, the subtleties of his work for the State Academy of Artistic Sciences and ”Great Soviet Encyclopedia,” teaching at the Higher State Literary Courses — and the chain of domestic and worldly problems comparably essential to his biography, which were set out in detail in the messages to one of the rare confidants. Letters are accompanied by comprehensive historical and literary commentary.